The Effect Of Use Of Birthing Ball On Reducing Back Pain Of Pregnant Women In Third Trimester At Kudus In 2023 - Rewanta Cahya Mita; Siti Muawanah; M. Zuhal Purnomo (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction Low back torment in third trimester pregnant ladies happens due to hormonal changes which cause changes within the supporting and interfacing delicate tissues coming about in diminished muscle flexibility and adaptability. Administration that can be done to diminish and avoid back torment can be done is Birthing ball. Birthing ball is the application of non-pharmacological torment administration that can be done by giving works out and works out to clients with back torment complaints that frequently occur in pregnancy, particularly within the third trimester of pregnancy. Objectives: : To determine the effect of using a birthing ball on reducing back pain in third trimester pregnant women at PMB Isni Handayani Utami. Methods: In this study experimental designs with a two group pretest-posttest design. Where measurements were taken before carrying out the treatment (pre-test), then giving birthing ball therapy to pregnant women in the third trimester for 1 month, namely once every week, after being given the intervention, measurements were made again (post-test). Analysis of research data using univariate and bivariate Mann-Whitney Results: Univariate analysis showed that the distribution of pre-test respondents was a moderate pain scale which was dominated by scale 4 which totaled 18 people (60%), scale 5 numbered 8 people (26.67%) and the smallest scale 6 amounted to 4 people (13, 33%). Then the birthing ball intervention was carried out and a post-test was carried out with the results of the mild pain scale category, namely scale 3 totaling 3 people (10%), scale 2 totaling 14 people (46.67%) and scale 1 totaling 13 people (43.33%) . Then the Mann-Whitney statistical test was carried out showing a sig(-2tailed) value = 0.0020 <0.05 so that it can be Conclusions: that the use of birthing balls has an effect on reducing back pain in third trimester pregnant women. Thus third trimester pregnant women who have complaints of low back pain are expected to do birthing balls as an effort to reduce low back pain.